The international consortium on the Ehlers–Danlos syndromes. Issue 1 (March 2017) - Bloom, Lara; Byers, Peter; Francomano, Clair; Tinkle, Brad; Malfait, Fransiska; ,
Abstract : Since 1998, two developments have led to concerns that the EDS nosology needs to be substantially revised. The first development was the clinical and molecular characterization of several new EDS variants, which substantially broadened the molecular basis underlying EDS. The second was the growing concern, in the absence of genetic diagnosis, that the hypermobile type of EDS had an expanded phenotype, may be genetically heterogeneous, and that the diagnostic criteria currently in use were inadequate. Furthermore, there is a dire need for the development of guidelines for management for each type of EDS to allow both the specialist and the generalist to care for affected individuals and their families. We have been meeting together as an international consortium over the past 2 years to establish these new criteria and management and care guidelines © 2017 Wiley Periodicals, Inc.